Assessment of parental mosaicism in SCN1A-related epilepsy by single-molecule molecular inversion probes and next-generation sequencing. Issue 2 (27th October 2018) - de Lange, Iris M; Koudijs, Marco J; van 't Slot, Ruben; Sonsma, Anja C M; Mulder, Flip; Carbo, Ellen C; van Kempen, Marjan J A; Nijman, Isaac J; Ernst, Robert F; Savelberg, Sanne M C; Knoers, Nine V A M; Brilstra, Eva H; et al.
Abstract : Background: Dravet syndrome is a severe genetic encephalopathy, caused by pathogenic variants in SCN1A. Low-grade parental mosaicism occurs in a substantial proportion of families (7%–13%) and has important implications for recurrence risks. However, parental mosaicism can remain undetected by methods regularly used in diagnostics. In this study, we use single-molecule molecular inversion probes (smMIP), a technique with high sensitivity for detecting low-grade mosaic variants and high cost-effectiveness, to investigate the incidence of parental mosaicism of SCN1A variants in a cohort of 90 families and assess the feasibility of this technique. Methods: Deep sequencing of SCN1A was performed using smMIPs. False positive rates for each of the proband's pathogenic variants were determined in 145 unrelated samples. If parents showed corresponding variant alleles at a significantly higher rate than the established noise ratio, mosaicism was confirmed by droplet digital PCR (ddPCR). Results: Sequence coverage of at least 100× at the location of the corresponding pathogenic variant was reached for 80 parent couples. The variant ratio was significantly higher than the established noise ratio in eight parent couples, of which four (5%) were regarded as true mosaics, based on ddPCR results. The false positive rate of smMIP analysis without ddPCR was therefore 50%. Three of these variants had previously been considered de novo in the proband by Sanger sequencing. Conclusion: smMIP technology combined withnext generation sequencing (NGS) performs better than Sanger sequencing in the detection of parental mosaicism. Because parental mosaicism has important implications for genetic counselling and recurrence risks, we stress the importance of implementing high-sensitivity NGS-based assays in standard diagnostics.